Syrian-American Relations under Current Circumstances - اسكيف, سامر (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aimed to explain Syrian-American relations under the current circumstances. To study the impact of the war on Syria on economic relations with countries hostile to Syria in the war, especially America, as well as to explain the impact of American sanctions on Syria, the researcher relied on the descriptive approach, and the researcher also relied on the historical approach by referring to the historical sequence of the development of international relations during the war period. On Syria, the researcher also relied on secondary data published in scientific and academic studies and research, reports issued by international institutions and scientific research, and data contained in the Central Bureau of Statistics. The researcher relied on the analytical approach in his study of the numbers for the research through time series analysis, and among the most important The results of the research: 1- The war on Syria in 2011 represented a turning point in international politics and the conflict between regional and international powers, which led to the prolongation of the war until the present time. 2-Syria's strategic location has made it a focus for the West's ambitions and exploitation of its role in regional and international balances. 3- The war on Syria is a war of the interests of major powers over influence and economic interests related to energy sources and methods of supplying them.